The Managerial Economics Implications Of Rupiah Exchange Rate Fluctuations On Investment And Corporate Growth - Napitupulu, Bertha Elvy; Rajagukguk, Juli Sinar Suriati; Siswono, Safitri (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2024)
The managerial economics implications of Rupiah exchange rate fluctuations on investment and corporate growth are critical considerations for businesses operating in Indonesia's volatile economic environment. This study, conducted through an extensive literature review, explores the multifaceted impacts of exchange rate volatility on corporate decision-making and performance. Key findings indicate that fluctuations in the Rupiah increase investment risks and uncertainties, adversely affecting private sector investment and corporate growth. The review highlights that exchange rate volatility escalates production costs and diminishes profit margins, thereby impeding business expansion and competitive positioning in international markets. From a managerial perspective, effective risk management strategies such as hedging and portfolio diversification are essential for mitigating exchange rate risks. Additionally, efficient resource management and operational efficiency are pivotal in cushioning the adverse effects of currency fluctuations. The study underscores the importance of dynamic pricing strategies and financial instruments in stabilizing cash flows and sustaining growth amidst economic turbulence. This paper contributes to the theoretical and practical understanding of exchange rate impacts on managerial decisions and provides actionable insights for businesses to navigate currency volatility. Future research should focus on empirical analyses to validate the findings and explore case studies across various sectors to further elucidate the nuances of managing exchange rate risks in different business contexts.